PENGARUH LAMA PEMASAKAN TERHADAP SIFAT SENSORI, SIFAT KIMIA, DAN SIFAT FISIK PERMEN JELLY SUSU KAMBING THE EFFECT OF COOKING LENGTH ON THE SENSORY PROPERTIES, CHEMICAL PROPERTIES, AND PHYSICAL PROPERTIES OF GOAT'S MILK JELLY CANDY - Alfi Syahriyah Majidah; susilawati -; Otik Nawansih (Jurnal Agroindustri Berkelanjutan, 2024)
Goat's milk jelly candy is a snack made from a mixture of sugar, goat's milk, thickening agents and other permitted food additives, which of course can increase consumption of goat's milk. Factors that can influence the quality of jelly candy include gelling ingredients, cooking temperature, cooking length, choice of mixed ingredients, addition of sugar, etc. The aim of this research is to determine the effect of cooking length on the sensory properties, chemical properties and physical properties of goat's milk jelly candy in accordance with SNI 3547-2-2008 concerning jelly candy. This research was structured in a Completely Randomized Block Design (CRBD) with a single factor and four replications. The factor used is the cooking length. Fresh goat's milk, carrageenan, gum arabic, glucose syrup, sugar, and water are mixed and cooked for a cooking length according to the treatment after the mixture boils, starting from 15, 20, 25, 30, 35, and 40 minutes. The research results show that the cooking length for jelly candy affects the sensory properties, chemical properties and physical properties of goat's milk jelly candy. The best cooking length for goat's milk jelly candy is 20 minutes with texture characteristics of 4.00 (chewy), color 4.38 (brownish yellow), taste 4.23 (like), aroma 3.87 (rather like), water content 11.28%, ash content of 0.82%, reducing sugar content of 5.70%, sucrose sugar content of 42.79%, and springiness level of 2.925 mm have met the jelly candy quality standards according to SNI No. 3547-2-2008 regarding jelly candy.